The 4000 Watt tennis player - Kibler, W. B. (Medicine and Science in Tennis, 2009)
The article deals with force generation in tennis, e.g. with forces and loads associated with tennis strokes and the kinetic energy and force generated in each kinetic chain segment, the force generation for tennis serving using "pull through" and the "push through" mechanism, force control, advantages and disadvantages of integrated activity and with clinical implications. Summary: Athletes integrate patterned coordination of muscle activations, coordinated generation and control of forces, and sequencing of joint position and motions to produce power and skillful athletic activities involving the shoulder and elbow in tennis strokes. The "4000 watt" tennis player is a player that has strong, forcing strokes, and is generating maximum power as a result of this integration. Alteration in this integrated mechanism is frequently associated with shoulder and elbow injury. Evaluation protocols can be devised to screen for proximal alterations, which then can be included in the treatment.